WEB-BASED SALE INFORMATION SYSTEM FOR POLLUX SHOES AT CV NOTO PUTRA - Zsendy Ernosa; Sumarno Sumarno; Cindy Taurusta; Suprianto Suprianto (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to analyze the digital transformation strategy of CV Noto Putra, a Surabaya-based footwear manufacturing company, in strengthening its competitiveness through the adoption of e-commerce platforms and legal compliance in online transactions. Method: The research applies a descriptive qualitative approach focusing on company practices related to technology adoption, marketing strategies, and adherence to Indonesia’s Civil Code in conducting digital business operations. Results: Findings indicate that the integration of e-commerce has enhanced operational efficiency, expanded market reach, and improved customer engagement. Furthermore, compliance with legal frameworks reinforces consumer trust and transaction transparency. Novelty: This study highlights how traditional manufacturing companies, such as CV Noto Putra, can leverage digital innovation combined with legal integrity to sustain competitiveness and achieve long-term business growth in Indonesia’s evolving footwear industry.